2009
DOI: 10.1089/jwh.2008.1275
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Absolute and Excessive Weight Gain During Pregnancy

Abstract: Objective: Factors associated with weight gain during pregnancy that may be linked to maternal overweight and obesity were examined. Methods: In this observational study, 144 women reported on demographics, (prepregnancy) body weight, and lifestyles in self-reported questionnaires at 30 weeks gestation. Body weight at the end of pregnancy (selfreported at 6 weeks postpartum) was used to determine total gestational weight gain. Multivariate prediction models were developed to identify factors associated with to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 38 publications
2
66
1
Order By: Relevance
“…But an expectant mother who herself had a high birth weight [83] and the body mass index of the expectant father were also found to be associated with excessive weight gain during pregnancy [72]. In addition, continued nicotine consumption [72,74], quitting smoking, and lack of physical activities [69,80,83] can also lead to excessive weight gain [83]. In contrast, regular physical activity during pregnancy can have a preventive effect on weight gain in pregnancy.…”
Section: Effects Of Malnutrition and Of Excessive Weight Gain Includimentioning
confidence: 99%
“…But an expectant mother who herself had a high birth weight [83] and the body mass index of the expectant father were also found to be associated with excessive weight gain during pregnancy [72]. In addition, continued nicotine consumption [72,74], quitting smoking, and lack of physical activities [69,80,83] can also lead to excessive weight gain [83]. In contrast, regular physical activity during pregnancy can have a preventive effect on weight gain in pregnancy.…”
Section: Effects Of Malnutrition and Of Excessive Weight Gain Includimentioning
confidence: 99%
“…For example, Williams et al (9) reported that both long and short sleep duration in early pregnancy were associated with elevated blood pressure in later pregnancy. Likewise, Althuizen et al (10) identified short sleep as a correlate of excessive weight gain in pregnancy. However, they only assessed sleep in later pregnancy (30 weeks’).…”
Section: Introductionmentioning
confidence: 99%
“…LTPA during pregnancy may aid women in achieving GWG within IOM recommended ranges, since LTPA contributes to energy balance. Data available from observational studies suggest that women reporting participation in LTPA may be more likely to experience an attenuation of GWG within recommended ranges 7, 11, 14 . Additionally, a recent meta-analysis investigated the effectiveness of LTPA interventions during pregnancy in modifying GWG and found that women participating in a LTPA intervention experienced less GWG 15 .…”
Section: Introductionmentioning
confidence: 99%